Energy Consumption Minimizing for Fixed-Wing UAV Inspection Systems with Kinematic Constraints - Zhang, Nanbin; Wu, Fahui; Xu, Yu; Xiao, Lin; Yang, Dingcheng; Ou, Longhui (IEEE/CIC International Conference on Communications in China - Workshops (Online), 2024)
In this paper, we consider a flight energy consumption model (FECM) for fixed-wing unmanned aerial vehicles (UAVs) under the consideration of the UAV flight rate, turn radius and heading changes. To validate the effectiveness of the proposed FECM, we study a UAV-based urdan environment patrol inspection system, where a fixed-wing UAV flies subject to kinematic and safety constrains. We aim to minimize the total energy consumption of UAV by jointly optimizing the UAV turn radius, frequency of heading change and inspection sequence. Due to the nonlinearity of the constraints and the nature of the combinatorial optimization problem, the formulated problem is non-convex, making it challenging to obtain its optimal solution. To tackle this issue, we decompose the original problem into two subproblems: 1) trajectory design between adjacent inspection points; and 2) optimal the patrol sequence among cruise points. An improved hybrid A* algorithm (IHA*A) is proposed to determine the optimal trajectory. Then we optimize the patrol sequence by genetic algorithm (GA) to determine the optimal traverse order. Simulation results demonstrate that the proposed algorithm significantly reduces energy consumption compared to the baseline scheme.